From Preaching Faith to Spreading the Virus: A Study of The Tablighi Jama’at in Pakistan - Ali, Kausar; Minxing, Huang (Technium Social Sciences Journal, 2020)
With the emergence of coronavirus disease or coronavirus pandemic, now popularly known as COVID-19, a new world-wide discussion started that religion and religious gatherings playing an active role in accelerating the spread of coronavirus in the world. If, on the one hand, religious gatherings were banned or at least limited in some Muslim countries while on the other hand, such faith-based gatherings have proven to be the hotbeds for outbreaks. The purpose of this study is to investigate the connection between the Tablighi Jama’at (TJ) and the coronavirus in Pakistan. It is believed that the participants carried the virus into different parts of Pakistan. This study finds that Tablighi Jamaat’s factor in the spread of coronavirus in Pakistan cannot be ignored. Shia pilgrims from Iran also brought the virus from Iran into Pakistan. The paper finds that this pandemic may once again raise the issue of sectarianism in the county. The present research finds that Islamists have always been supported by the state. Now it has become very difficult for state policy-makers to resist them in the present fight against the coronavirus.